The Role of Plasma, Platelets, and Growth Factors in Knee Osteoarthritis: The Evidence-Based Medicine 2022 - Cheeva-akrapan, MD, Vorasilp; Turajane, MD, Thana (Journal of Southeast Asian Orthopaedics, 2022)
Knee osteoarthritis greatly affects the quality of life of numerous people worldwide. Study in 2020 estimated that the global incidence of knee osteoarthritis was 203 per 10,000 person-years and the global prevalence was 16%. Biologic derivatives, such as plasma, platelets, and growth factors, have gained popularity due to their efficacy and safety; however, several controversies related to the treatment of knee osteoarthritis with orthobiologics still exist. The purpose of this review is to provide recent evidence about the use of growth factors as orthobiologics for the treatment of knee osteoarthritis, to summarize the up-to-date clinical practice guidelines provided by American Academy of Orthopedic Surgeons (AAOS) and American College of Rheumatology (ACR), and to discuss these guidelines based on the latest research.